Prevalence of anemia amongst preschool children in rural field practice area of medical college, Mumbai, Maharashtra - Bandi, Janardhan R.; Bari, Sanket A. (International Journal Of Community Medicine And Public Health, 2018)
Background: Anemia is a public health problem all over globe affecting both developed and developing countries. A situational analysis of local field practice area could ensure proper planning of preventive strategies. The objectives of the study were to assess the prevalence and distribution of anemia in preschool children in rural field practice area of medical college, Mumbai. Methods: A cross-sectional study was conducted amongst 280 preschool children in the field practice area of Department of Community Medicine of T. N. Medical College, Mumbai during the period of May 2016 to April 2017. Hemoglobin colour scale indicator was used to grade the anemia. Results: Majority of children had mild anemia (43.93%) followed by moderate to severe anemia. Female children had (23.21%) mild anemia followed by (18.93%) moderate anemia and (2.86%) severe anemia. Male children had (20.71%) mild anemia followed by (16.07%) moderate anemia and (3.21%) severe anemia. There was no significant association of anemia with gender in pre-school children. Age, religion, socio-economic status and parent’s education showed significant association with presence of anemia. Conclusions: Anemia still remains a public health problem in the rural area. Early and targeted interventions with regular follow up need to be undertaken at grass root level to reduce its prevalence in the population.